(untitled) (Global Journal of Science Frontier Research, 2024)
This research is on natural convection flow of a fluid through a circular plate on a two-dimensional square body In this paper heat transfer of laminar flow will be investigated based on mesh modeling and graphs under heat flux and viscosity Temperatures thermal conductivity velocity components viscous dissipation of fluid with time are used as variables A flat square surface with circle is considered in the investigation by using COMSOLMULTIPHYSICS Here square body and circular plate are insulated As material we have used water The parameters of the fluid have inlet velocity outlet velocity heat flux and thermal conductivity Using boundary condition and velocity components with temperature we can solve governing equations numerically The solution has been expressed as meshes and graphs in the results Different sectors of science like magneto hydrodynamic fluid flow natural convection Radiation solar engineering and medical science will be benefitted by this research We construct many mesh models through our studied technique which is shown in Figure a to o We will also discuss 2D graphical representation through the proposed technique which is shown in Figures p to t In future we may try to apply our results in space heating domestic hot or cold water processes heat from electricity and many other related fields